Analisis Budaya Organisasi di Kantor Badan Pemeriksa Keuangan Perwakilan Provinsi Gorontalo - Alya Amirunnisa Pusadan; Irawaty Igirisa; Fenti Prihatini Dance Tui (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
This research aims to analyze the organizational culture at the Representative Office of the Audit Board of the Republic of Indonesia in Gorontalo Province. This research uses a qualitative research approach. The data collection techniques include observation, interviews, and documentation. The data analysis techniques involve data reduction, data presentation, and conchading. The results of the research indicate that the organizational culture at the Representative Office of the Audit Board of the Republic of Indonesia in Gorontalo Province is analyzed hased on the research focus and sub-focus, which involves seven principles of organizational culture, such as innovation, the team orientation, the result orientation, and the member orientation. Morcover, the principle of aggressiveness has been well-implemented, Furthermore, the principle of innovation is demonstrated by the existence of web pages for cach sub-division that the employees can access. The principle of meticulousness is shown in the public relations division, where employees must carefully draft letters, particularly in the letters' numbering system. Additionally, the principle of team orientation is observed, where employees are divided into groups tasked with conducting audits in the Gorontalo Province. These groups focus on both result orientation and member orientation. Result orientation includes work plans that most be achieved within five years, while member orientation includes the requirement for employees to participate in training to develop their capacities. The principle of aggressiveness is reflected in how all employees are expected to meet deadlines to achieve the set targets. However, the principle of courage is not yet fully optimized because some employees hesitate to try new things and are reluctant or fearful to express their opinions.